2020
DOI: 10.1097/fm9.0000000000000071
|View full text |Cite
|
Sign up to set email alerts
|

Human Coronavirus Infections and Pregnancy

Abstract: Human coronavirus (HCoV) causes potentially fatal respiratory disease. Pregnancy is a physiological state that predisposes women to viral infection. In this review, we aim to present advances in the pathogenesis, clinical features, diagnosis, and treatment in HCoV in pregnancy. We retrieved information from the Pubmed database up to June 2020, using various search terms and relevant words, including coronaviruses, severe acute respiratory syndrome coronavirus, Middle East respiratory syndrome coronavirus, 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 112 publications
1
12
0
Order By: Relevance
“…A second review study published in 2021 comparing outcomes between pregnant and non-pregnant women with SARS-CoV-2, MERS (Middle East respiratory syndrome coronavirus) and SARS (Severe acute respiratory syndrome coronavirus) concluded that there is no evidence that pregnant women are more susceptible to coronavirus infection in general, or that those infected with these viruses are more likely to develop severe pneumonia. Similar to non-pregnant women, pregnant women with MERS had the highest mortality, followed by those with SARS and COVID-19 [33]. These findings are corroborated by a retrospective and multicentric cohort carried out in 2020 [34] in which it was observed that the mortality rate among pregnant women (110 patients) compared to non-pregnant women (224 patients) did not show statistically significant differences.…”
Section: Discussionsupporting
confidence: 52%
“…A second review study published in 2021 comparing outcomes between pregnant and non-pregnant women with SARS-CoV-2, MERS (Middle East respiratory syndrome coronavirus) and SARS (Severe acute respiratory syndrome coronavirus) concluded that there is no evidence that pregnant women are more susceptible to coronavirus infection in general, or that those infected with these viruses are more likely to develop severe pneumonia. Similar to non-pregnant women, pregnant women with MERS had the highest mortality, followed by those with SARS and COVID-19 [33]. These findings are corroborated by a retrospective and multicentric cohort carried out in 2020 [34] in which it was observed that the mortality rate among pregnant women (110 patients) compared to non-pregnant women (224 patients) did not show statistically significant differences.…”
Section: Discussionsupporting
confidence: 52%
“…The Chinese guidelines highlight the separation of the newborn from the mother and no maternal breast milk use [ 28 ]. Newborns born to mothers with confirmed SARS-CoV-2 infection should be considered patients under investigation until test results arrive [ 29 ]. As the pandemic started, our Clinic of Neonatology approach was to separate the mother and infant at birth and require breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that SARS-CoV-2 infection in pregnant women behaves similarly to the general population, contrary to what has been reported with other types of coronavirus infection in the past ( Li N. et al, 2020 ; Yang et al, 2020 ; Fan et al, 2021 ). The disease manifests itself with typical symptoms and occurs with different degrees of severity, such as mild disease in 81–86% of cases, severe disease in 9.3–14%, and critical disease in 5%; values close to those reported in the general population (80, 15, and 5%, respectively) ( Han et al, 2020 ).…”
Section: Clinical Presentation Of Severe Acute Respiratory Syndrome C...mentioning
confidence: 67%